Analysis of tumour responses by excision and in vitro assay of cellular clonogenic capacity. - Barendsen, G. W. (Nature Publishing Group, 1980)
A review is presented of the advantages and problems associated with the use of in vitro assays of cellular clonogenic capacity when used to analyse responses of tumours treated in vivo, either with radiation or chemotherapeutic agents. Three questions are considered: (1) Does the cell suspension obtained by the dispersion technique from various types of solid tumours provide an adequately random sample of the cells initially present in the tumour? (2) Are the properties of cells in suspensions obtained from solid tumours assayed in optimal conditions in vitro? (3) Are the properties expressed and analysed by in vitro techniques equivalent to the properties that the same cells would have expressed if they had been left in vivo, either in untreated or in treated tumours? It is concluded that the in vitro assay provides a valuable tool to analyse tumour responses but that the data obtained must be complemented by information on cell kinetics and other factors to obtain a complete description of tumour responses and to correlate them with tumour curability and growth delay.